Board Attributes and Social and Environmental Performance. Evidence from The Energy Sector - Pompei Mititean (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- Does corporate governance have an impact on the social and environmental performance of companies in the energy industry? Motivation- Companies have been oriented in recent years to obtain not only financial performance, but also other aspects, such as social and environmental performance, which are important in the activity of attracting new investors. The environmental and social performance of companies is critical in the activity of attracting new investors, with investors drawn to companies that report more information about how the company participates in social campaigns and how it considers environmental issues. From this perspective and considering legislation relating to reducing the impact of waste and emissions on the environment and the way companies respect the workforce, human rights and society in general, board decisions may be influenced. Data- Data were collected from the Thomson Reuters database for a sample of 266 companies during the period 2016-2020, consisting of 1.330-year observations. Tool- The SPSS statistical program was used to run the regression models for the selected sample. Findings- The results show that the size of the board has a positive and significant impact on environmental performance, while for social performance it has an insignificant positive impact. Additionally, gender diversity and board independence have a significant negative impact on social and environmental performance. Practical implications- This study complements and supports the existing literature on this relationship in the energy sector. The study has practical implications for investors in their decision making and for board members.
Keywords: G34; M41; P18; 650; Board size; board gender diversity; board independence; social and environmental score; energy industry